The influence of poverty on children's school experiences: pupils' perspectives. (1st October 2019) - Naven, Lynn; Egan, James; Sosu, Edward M.; Spencer, Sara
Abstract : This study examined the potential influence of policies and practices on the ability of children from low-income families to participate fully in the school day. Pupils from six schools participated in 71 focus groups and revealed a range of barriers affecting their school experience: transport costs and limited support; clothing costs, stigma and enforcement of school dress codes; material barriers to learning at school and home; concerns about free school meals; missing out on school trips, clubs and events.Findings on school uniform were an important catalyst towards a recent policy change in Scotland in increasing the school clothing grant.